Delphi study on country-of-origin labelling for processed foods - Jenny Yuezhen Su; Maurizio Canavari (Agricultural and Food Economics, 2018)
In the international scene, country-of-origin labelling (COOL) is a controversial issue. We aim at defining criteria for the country-of-origin marking COOL for processed foods and figure out the effect of COOL on international trade. We conduct qualitative and systematic research using the Delphi method. The panel of experts in food labelling and food policy was composed of 19 members in 13 countries. The experts actively discussed topics ranging from the possible protectionism of COOL to the desirability of worldwide standardisation of COOL, providing comprehensive perspectives on the issues concerning COOL. The essential consensus is that multiple countries of origin marking can give accurate information about the origin of food produced by two or more countries, avoiding misinformation for consumers. This research provides valuable insights for the formulation of COOL policy in various countries. The main limitation is due to the absence of the view of producer associations.
Keywords: 330; Country of origin; Labelling; Processed foods; International trade; Delphi study; COOL policy